ANALISIS PERILAKU PHUBBING PADA MAHASISWA FAKULTAS KEGURUAN DAN ILMU PENDIDIKAN UNIVERSITAS MUHAMMADIYAH MATARAM - Taufiqurrahman Taufiqurrahman; Siti Sanisah; Arif Arif; Muharini Muharini; Khosi’ah Khosi’ah; Nurin Rochayati (Universitas Hamzanwadi, 2024)
The phenomenon of phubbing today is very obvious in everyday life, the impact of the progress of civilization is supported by the development of science and technology so that humans are increasingly dependent on technological products such as mobile phones. This quantitative research using the survey method with a cross-sectional study system aims to conduct an in-depth study of the phenomenon of phubbing in the student environment. A sample of 152 people was determined by purposive sampling. The research data were obtained from the response of the sample to the questionnaire supported by observation, interviews, and documentation and analyzed using descriptive methods. The results showed that the level of student phubbing was in the medium category. It is recommended that students can make self-regulation in the use of cell phones to minimize the level of phubbing, especially when studying and talking to others.